Repeatability of Radiomic Features in Non-Small-Cell Lung Cancer [18F]FDG-PET/CT Studies: Impact of Reconstruction and Delineation - van Velden, Floris H. P.; Kramer, Gerbrand M.; Frings, Virginie; Nissen, Ida A.; Mulder, Emma R.; de Langen, Adrianus J.; Hoekstra, Otto S.; Smit, Egbert F.; Boellaard, Ronald (Molecular imaging and biology, 2016)
Purpose To assess (1) the repeatability and (2) the impact of reconstruction methods and delineation on the repeatability of 105 radiomic features in non-small-cell lung cancer (NSCLC) 2-deoxy-2-[ 18 F]fluoro-D-glucose ([ 18 F]FDG) positron emission tomorgraphy/computed tomography (PET/CT) studies. Procedures Eleven NSCLC patients received two baseline whole-body PET/CT scans. Each scan was reconstructed twice, once using the point spread function (PSF) and once complying with the European Association for Nuclear Medicine (EANM) guidelines for tumor PET imaging. Volumes of interest ( n = 19) were delineated twice, once on PET and once on CT images. Results Sixty-three features showed an intraclass correlation coefficient ≥ 0.90 independent of delineation or reconstruction. More features were sensitive to a change in delineation than to a change in reconstruction (25 and 3 features, respectively). Conclusions The majority of features in NSCLC [ 18 F]FDG-PET/CT studies show a high level of repeatability that is similar or better compared to simple standardized uptake value measures.